2022
DOI: 10.1007/s11604-022-01293-y
|View full text |Cite
|
Sign up to set email alerts
|

Image quality evaluation of real low-dose breast PET

Abstract: Purpose To evaluate the clinical feasibility of high-resolution dedicated breast positron emission tomography (dbPET) with real low-dose 18F-2-fluorodeoxy-d-glucose (18F-FDG) by comparing images acquired with full-dose FDG. Materials and methods Nine women with no history of breast cancer and previously scanned by dbPET injected with a clinical 18F-FDG dose (3 MBq/kg) were enrolled. They were injected with 50% of the clinical 18F-FDG dose and scanned with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In recent years, breast imaging diagnostics have advanced significantly, with improvements in imaging technology and diagnostic accuracy [27][28][29][30][31][32]. This progress is not only due to enhancements in the quality of mammography and ultrasound images and the establishment of more refined reading techniques but also to the emergence of new modalities such as contrast-enhanced Magnetic Resonance Imaging (MRI), Positron Emission Tomography/Computed Tomography (PET/CT), and PET mammography.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, breast imaging diagnostics have advanced significantly, with improvements in imaging technology and diagnostic accuracy [27][28][29][30][31][32]. This progress is not only due to enhancements in the quality of mammography and ultrasound images and the establishment of more refined reading techniques but also to the emergence of new modalities such as contrast-enhanced Magnetic Resonance Imaging (MRI), Positron Emission Tomography/Computed Tomography (PET/CT), and PET mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even images with fewer RI counts caused by reduced FDG dose can be improved. A previous study on actual low-dose dbPET revealed that a clinically acceptable image quality is obtained at approximately 25–50% of the dose for conventional whole-body FDG PET [ 15 ]. In this study, images were sampled from the start time of collection; thus, the earlier the start time of acquisition, the higher the RI counts, and the later the start time of acquisition, the lower the RI counts, even within the same minute.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a very complicated method, and in practice, it is difficult to do in each case. Therefore, we chose this simple method used in a previous study [ 15 ]. Accordingly, we can approximately assume that (A% acquisition times) × (B% dose) image” = “(B% acquisition times) × (A% dose) image.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation